The Validity of Tarot as a Personality Inventory - Santosa, Dimas Armand (ANIMA Indonesian Psychological Journal, 2012)
Tarot is mainly known by the general population as a divination media while in reality, it is also usable to measure the personality of individuals by using the personality categories based on the Tarot major arcanes (Ouspensky, 1976; Levitt, 2003; Mathers, 2004). The goal of this research was to test the validity of Tarot as an alternative personality inventory by comparing it with the Big Five Personality score measured by using International Personality Item Pool (IPIP) on each personality category based on Tarot. The subjects of this research were 494 psychology students from the 2008-2011 generation. In order to determine the subjects’ Tarot personality categories, the subjects’ birth date were used, and in order to measure the Big Five Personality score, IPIP was used. Results show that there were no significant differences between the Big Five Personality aspects score on each Tarot personality categories. The scores of ANOVA and cross-tabbing between each Tarot personality categories do not show any significant differences, meaning that Tarot is not sufficient to be used as an alternative personality inventory. Tarot lebih banyak dikenal oleh masyarakat umum sebagai media meramal. Sebenarnya Tarot juga dapat digunakan untuk mengukur kepribadian seseorang dengan menggunakan kategori kepribadian berdasarkan major arcana Tarot (Ouspensky 1976; Levitt, 2003, Mathers, 2004). Tujuan penelitian ini adalah menguji tingkat validitas Tarot sebagai alat pengukur kepribadian alternatif dengan membandingkan skor Big Five Personality yang didapat menggunakan International Personality Item Pool (IPIP) antar-kategori kepribadian berdasarkan Tarot. Subjek penelitian adalah 494 mahasiswa fakultas psikologi angkatan 2008-2011. Teknik pengukuran menggunakan tanggal lahir subjek untuk menentukan kategori kepribadian Tarot dan IPIP untuk mendapatkan skor Big Five Personality. Hasil penelitian ini menunjukkan bahwa tidak ada perbedaan skor aspek Big Five Personality antar-kategori kepribadian berdasarkan Tarot. Skor ANOVA dan cross-tabbing menunjukkan bahwa tidak ada perbedaan skor aspek Big Five Personality antar- kategori kepribadian berdasarkan Tarot. Hasil ini menunjukkan bahwa Tarot belum dapat digunakan sebagai alat pengukur kepribadian alternatif yang signifikan.